The texts in elementary classrooms / edited by James V. Hoffman, Diane L. Schallert. - Hoffman, James V.; Schallert, Diane L. (Center for Improvement of Early Reading Achievement (Series), 2004)
This volume explores a variety of topics, including: texts in the teaching and learning of reading; word identification and text characteristics; choosing fiction to support young children's literacy development; electronic text in the classroom; and issues surrounding text selection.